Interaksi Sosial Dan Komunikasi Pada Pesta Tahunan (Bona Taon) Dalam Perkumpulan Keturunan Sianturi Pramassahati - Leonardo, Julio; Poerana, Ana Fitriana; Budhiharti, Tri Widya (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to examine how the communication patterns that occur at parties (Bona Taon) in this tradition, culture is an interrelated goal and cannot be replaced by another because this culture develops from generation to generation. In the descendants of Sianturi Pramassahati there is a tradition, namely the annual clan (Bona Taon), not only a small association but an association that involves many members so that a communication network is needed that forms a communication pattern. The results of this research show that the communication patterns of Sianturi Pramassahati descendants in the feast (Bona Taon) are pre-Easter and post-event communication, communication between the older and younger generations and introducing culture, traditions and advice through stories from parents to the younger generation, so that they can act as guardians. traditions or continuation of traditions, ritual communication such as traditional ceremonies, prayers, social communication, namely eating together, meeting with members of the extended family with the aim of strengthening social networks and cooperation and the use of media technology with the aim of documenting and sharing events on social media in order to introduce the clan and culture. Batak..